Peer reviewed evaluation of registered end-points of randomised trials (the PRE-REPORT study): protocol for a stepped-wedge, cluster-randomised trial. Issue 5 (1st June 2019) - Jones, Christopher W; Adams, Amanda; Weaver, Mark A; Schroter, Sara; Misemer, Benjamin S; Schriger, David; Platts-Mills, Timothy F
Abstract : Introduction: Clinical trials are critical to the advancement of medical knowledge. However, the reliability of trial conclusions depends in part on consistency between pre-planned and reported study outcomes. Unfortunately, selective outcome reporting, in which outcomes reported in published manuscripts differ from pre-specified study outcomes, is common. Trial registries such as ClinicalTrials.gov have the potential to help identify and stop selective outcome reporting during peer review by allowing peer reviewers to compare outcomes between registry entries and submitted manuscripts. However, the persistently high rate of selective outcome reporting among published clinical trials indicates that the current peer review process at most journals does not effectively address the problem of selective outcome reporting. Methods and analysis: PRE-REPORT is a stepped-wedge cluster-randomised trial that will test whether providing peer reviewers with a summary of registered, pre-specified primary trial outcomes decreases inconsistencies between prospectively registered and published primary outcomes. Peer reviewed manuscripts describing clinical trial results will be included. Eligible manuscripts submitted to each participating journal during the study period will comprise each cluster. After an initial control phase, journals will transition to the intervention phase in random order, after which peer reviewers will be emailed registry information consisting of the date of registration and any prospectively defined primary outcomes. Blinded outcome assessors will compare registered and published primary outcomes for all included trials. The primary PRE-REPORT outcome is the presence of a published primary outcome that is consistent with a prospectively defined primary outcome in the study's trial registry. The primary outcome will be analysed using a mixed effect logistical regression model to compare results between the intervention and control phases. Ethics and dissemination: The Cooper Health System Institutional Review Board determined that this study does not meet criteria for human subject research. Findings will be published in peer-reviewed journals. Trial registration number: ISRCTN41225307 ; Pre-results.